Pelatihan Jurnalistik Filantropi Islami Bagi Eksekutif Kantor Layanan Lazismu Se-kabupaten Jember (Jurnal Suluah Komunitas, 2021)
Community Service Program (PPM) is implemented to help increase the acquisition of donations through the payment of zakat, infaq, and shadaqah, at LAZISMU Jember Regency, through branding activities by utilizing various media, both online and social media. This Community Service Program aims to empower amilin officers from LAZISMU Jember, to be more creative and innovative in raising donations from muzaki or donors. This method of devotion is carried out by providing training in philanthropic journalism, ranging from human interest-based news writing techniques, interesting activity photo selection techniques, and publication techniques, by utilizing online media and various social media platforms. The target of this activity is the executives of Lazismu Service Office (KLL) in Jember Regency. So far, LAZISMU executives have acted in accordance with the program. Includes publication of activities through social media. However, the acquisition of ZIS funds raised has not been optimal. Therefore, more creative and innovative fundraising activities are needed, including through more massive publicity activities, to raise public awareness, especially Muslims donating, by issuing zakat, infaq, and shadaqah funds, which are paid through ammil institutions, including LAZISMU Jember.